Design of Phthalocyanine‐Nanoparticle Hybrids for Photodynamic Therapy Applications in Oxygen‐Deficient Tumour Environment. Issue 31 (16th August 2019) - Nwahara, Nnamdi; Managa, Muthumuni; Prinsloo, Earl; Nyokong, Tebello
Abstract: The results show that coupling MnO2 with either AuNPs or AuNPs to phthalocyanines results in composites that significantly enhance the photodynamic therapy activity towards hypoxic MCF‐7 cancer cells. The preliminary findings from this study highlight the potential of phthalocyanines nanocomposites in reversing hypoxia‐triggered PDT resistance, and therefore, contribute to the design of hypoxia‐responsive tumour therapy systems. Abstract : A zinc metallophthalocyanine is linked to graphene quantum dots followed by in situ synthesis of MnO2 alone or with gold nanoparticles or silver nanoparticles, forming nanoconjugates for use in photodynamic therapy of cancer in hypoxia environment. The nanoconjugates significantly enhance the photodynamic therapy activity of the phthalocyanine towards hypoxic Michigan Cancer Foundation‐7 cancer cells.